2007
DOI: 10.4049/jimmunol.178.9.5735
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D Interaction with TLR5 Is Required for Inflammatory Signaling in Response to Bacterial Flagellin

Abstract: Protein kinase D (PKD), also called protein kinase C (PKC)μ, is a serine-threonine kinase that is involved in diverse areas of cellular function such as lymphocyte signaling, oxidative stress, and protein secretion. After identifying a putative PKD phosphorylation site in the Toll/IL-1R domain of TLR5, we explored the role of this kinase in the interaction between human TLR5 and enteroaggregative Escherichia coli flagellin in human epithelial cell lines. We report several lines of evidence that implicate PKD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 41 publications
4
49
0
Order By: Relevance
“…This difference is conceivably caused by the fact that mouse macrophages do not express the flagellin binding site TLR5, whereas human monocytes do (40), as also supported by the strong production of IL-8 induced by flagellin (see Figs. 3C and 5C), consistent with TLR5 activation (41). Not only PAMPs but also DAMPs, such as MSU, elicit a P2X 7 R-dependent IL-1␤ secretion, in contrast with a previous observation (22) that blocking P2X 7 R did not affect the MSU-induced release of IL-1␤.…”
Section: Discussionsupporting
confidence: 86%
“…This difference is conceivably caused by the fact that mouse macrophages do not express the flagellin binding site TLR5, whereas human monocytes do (40), as also supported by the strong production of IL-8 induced by flagellin (see Figs. 3C and 5C), consistent with TLR5 activation (41). Not only PAMPs but also DAMPs, such as MSU, elicit a P2X 7 R-dependent IL-1␤ secretion, in contrast with a previous observation (22) that blocking P2X 7 R did not affect the MSU-induced release of IL-1␤.…”
Section: Discussionsupporting
confidence: 86%
“…PKCe deficient mice had defects in clearance of both Gram-positive (TLR2) and Gram-negative (TLR4) bacterial infections. In an other study, activation of PKC isoforms by TLR5 through flagellin contributes to production of inflammatory cytokines in epithelial cells [45]. Besides, PKCa has been shown to control TLR2 dependent activation of NF-kB [46].…”
Section: Discussionmentioning
confidence: 93%
“…DICAM has one putative binding site for protein kinase C (PKC)-m in the extracellular juxta-transmembrane region (19) and recent studies have demonstrated the involvement of PKC-m in p38 MAP kinase-mediated signaling. (29,30) However, rDICAM containing only the extracellular domain inhibited osteoclast differentiation, which was rescued by high-dose M-CSF, implying that DICAMmediated inhibition of osteoclastogenesis is mostly through integrin b3 signaling. In the ''outside-in'' signaling model that connects integrin b3 and p38 MAP kinase, integrin first activates c-Src and consequently phosphorylates PLC-g. (4) When we assessed c-Src phosphorylation induced by RANKL, the phosphorylation of c-Src was not attenuated, but rather was slightly upregulated by DICAM (data not shown).…”
Section: Discussionmentioning
confidence: 99%